2008
DOI: 10.1007/s00415-008-0817-7
|View full text |Cite
|
Sign up to set email alerts
|

The realistic yield of lower leg SNAP amplitudes and SRAR in the routine evaluation of chronic axonal polyneuropathies

Abstract: To confirm distal axonal polyneuropathy in routine clinical practice the sural and superficial peroneal SNAP had equal and complementary yield, whereas the SRAR and dorsal sural SNAP had limited additional yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
1
13
1
1
Order By: Relevance
“…The diagnosis of CIAP was defined according to the following criteria (4,6): presence of symmetrical distal sensory or sensorimotor symptoms such as numbness, pins and needles, tightness, coldness, unsteadiness, muscle cramps, and weakness with onset in the lower limbs, compatible with polyneuropathy; presence of symmetrical distal sensory or sensorimotor signs with evidence of large nerve fiber involvement such as decreased sense of touch, vibration, and propriocepsis, usually in the presence of decreased pin prick/temperature sense, decreased/absent tendon reflexes, or slight muscle weakness on neurologic examination, compatible with polyneuropathy; an insidious onset and slow or no progression of the polyneuropathy over the course of at least 6 months; no identifiable cause for the polyneuropathy after thorough history-taking, clinical examination, and extensive laboratory testing; no suggestion of a hereditary polyneuropathy based on detailed kinship history (i.e., one or more affected family member), neurologic examination, or confirmation by genetic analysis; and nerve conduction studies excluding a demyelinating polyneuropathy and confirming large nerve fiber involvement if the findings on neurologic examination were equivocal considering the patient’s age (1619). Electrophysiological criteria for demyelination provided that distal compound motor action potential (CMAP) baseline to negative peak amplitude >1 mV were: reduction of motor nerve conduction velocity to <80% of lower limit of normal value (LLN) if distal CMAP >80% of LLN, or to <70% of LLN if CMAP was <80% of LLN; prolongation of distal motor latency to >125% of upper limit of normal value (ULN) if CMAP >80% of LLN, or to >150% of ULN if CMAP <80% of LLN; prolongation of F-waves to >120% of ULN if CMAP >80% of LLN, or to >150% of ULN if CMAP <80% of LLN; conduction block >50% area reduction or, in upper limb nerves, >30% amplitude reduction in proximal CMAP relative to distal; and abnormal temporal dispersion in upper limb nerves >30% duration increase or in lower limb nerves >100% duration increase in proximal CMAP relative to distal (20).…”
Section: Methodsmentioning
confidence: 99%
“…The diagnosis of CIAP was defined according to the following criteria (4,6): presence of symmetrical distal sensory or sensorimotor symptoms such as numbness, pins and needles, tightness, coldness, unsteadiness, muscle cramps, and weakness with onset in the lower limbs, compatible with polyneuropathy; presence of symmetrical distal sensory or sensorimotor signs with evidence of large nerve fiber involvement such as decreased sense of touch, vibration, and propriocepsis, usually in the presence of decreased pin prick/temperature sense, decreased/absent tendon reflexes, or slight muscle weakness on neurologic examination, compatible with polyneuropathy; an insidious onset and slow or no progression of the polyneuropathy over the course of at least 6 months; no identifiable cause for the polyneuropathy after thorough history-taking, clinical examination, and extensive laboratory testing; no suggestion of a hereditary polyneuropathy based on detailed kinship history (i.e., one or more affected family member), neurologic examination, or confirmation by genetic analysis; and nerve conduction studies excluding a demyelinating polyneuropathy and confirming large nerve fiber involvement if the findings on neurologic examination were equivocal considering the patient’s age (1619). Electrophysiological criteria for demyelination provided that distal compound motor action potential (CMAP) baseline to negative peak amplitude >1 mV were: reduction of motor nerve conduction velocity to <80% of lower limit of normal value (LLN) if distal CMAP >80% of LLN, or to <70% of LLN if CMAP was <80% of LLN; prolongation of distal motor latency to >125% of upper limit of normal value (ULN) if CMAP >80% of LLN, or to >150% of ULN if CMAP <80% of LLN; prolongation of F-waves to >120% of ULN if CMAP >80% of LLN, or to >150% of ULN if CMAP <80% of LLN; conduction block >50% area reduction or, in upper limb nerves, >30% amplitude reduction in proximal CMAP relative to distal; and abnormal temporal dispersion in upper limb nerves >30% duration increase or in lower limb nerves >100% duration increase in proximal CMAP relative to distal (20).…”
Section: Methodsmentioning
confidence: 99%
“…Nerve conduction studies and needle electromyography (EMG), collectively referred to as electrodiagnostic study (EDX) have traditionally been used to confirm the diagnosis of PN . Although large prospective studies of accuracy are lacking, the sensitivity of EDX has been estimated at approximately 70% . Confounding these estimations is the presence of exclusively or predominantly small fiber neuropathies, for which EDX is unrevealing, because small nerve fibers (as those found intraepidermally) are not amenable to traditional nerve conduction studies …”
Section: Introductionmentioning
confidence: 99%
“…[6] In one study, they observed that in 26% of their referents dorsal sural SNAP was not obtained, so they concluded that dorsal sural SNAP did not add to the diagnosis of a distal peripheral neuropathy. [22] In our population, there appears to be a risk factor of sitting cross legged on the floor for long hours, which may cause a focal neuropathy of the dorsal sural nerve. This needs to be investigated by further studies.…”
Section: Discussionmentioning
confidence: 88%